2022
DOI: 10.15585/mmwr.mm7126e2
|View full text |Cite
|
Sign up to set email alerts
|

Interim Recommendations of the Advisory Committee on Immunization Practices for Use of Moderna and Pfizer-BioNTech COVID-19 Vaccines in Children Aged 6 Months–5 Years — United States, June 2022

Abstract: On June 18, 2022, ACIP voted 12 to 0 (three members absent) in favor of the interim recommendation for the use of the Moderna COVID-19 vaccine for children aged 6 months-5 years. ACIP voted 12 to 0 (three members absent) in favor of the interim recommendation for the use of the Pfizer-BioNTech COVID-19 vaccine for children aged 6 months-4 years. ModernaTX, Inc.) in persons aged ≥18 years, and the Moderna COVID-19 vaccine is also recommended under EUA for children and adolescents aged 6-17 years (1). On August … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 16 publications
(17 reference statements)
2
47
0
2
Order By: Relevance
“…A minority of children with respiratory disease presented with croup. Our findings highlight the vulnerability of young children to COVID-19 hospitalizations and support the recent Advisory Committee on Immunization Practices recommendations for use of COVID-19 vaccine in children 6 months–4/5 years [ 23 ].…”
Section: Discussionsupporting
confidence: 85%
“…A minority of children with respiratory disease presented with croup. Our findings highlight the vulnerability of young children to COVID-19 hospitalizations and support the recent Advisory Committee on Immunization Practices recommendations for use of COVID-19 vaccine in children 6 months–4/5 years [ 23 ].…”
Section: Discussionsupporting
confidence: 85%
“…The Advisory Committee on Immunization Practices recommends that all persons aged ≥6 months receive a COVID-19 vaccine (8). Initial vaccine safety monitoring in children aged 6 months-5 years are usually similar to those described in clinical trials, and no unexpected safety concerns were detected (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…these age groups are authorized to receive a smaller amount of mRNA COVID-19 vaccine than are older children(8); incorrect dosing by vaccine administrators in different childhood age groups might lead to vaccination errors.…”
mentioning
confidence: 99%
“…6 In addition to being safe in pregnancy, other studies have shown that mRNA COVID-19 vaccines are effective www.thelancet.com/infection Published online August 11, 2022 https://doi.org/10.1016/S1473-3099(22)00443-1 at reducing the risk of severe illness in pregnant people and the risk of COVID-19 hospital admission among their infants younger than 6 months. 6,8 Protection in infants born to people vaccinated during pregnancy is particularly important because while mRNA COVID-19 vaccines were approved by the FDA on June 17, 2022, and recommended by the CDC on June 18, 2022, for children aged between 6 months and 5 years, 9 there are not currently any vaccines available for infants younger than six months.…”
Section: Safety Of Mrna Covid-19 Vaccines During Pregnancymentioning
confidence: 99%